Odpowiedzi

2009-12-27T09:49:35+01:00
2x-3y=6
x+2y=7

2x-3y=6
-2x-4y=-14

-7y=-8
y=8/7

2x-3*8/7=6
2x=66/7
x=33/7

x=4 5/7
y=8/7
2009-12-27T09:52:16+01:00
2x-3y=6 / *2
x+2y=7 / * 3

4x-6y=12
3x+6y=21 +
------------------

7x = 33 / 7
x = 4,71

x+2y=7
x=4,71

4.71+2y=7
x=4,71

2y=7-4,71
x=4,71

2y=2,29 /2
x=4,71

y=1,145
x=4,71



( UWAGA ! to jest w przybliżeniu bo 33/7=4,714285714286 )
2009-12-27T10:03:55+01:00
2x-3y=6
x+2y=7 / * (-2)

2x-3y = 6
-2x -4y = -14

-7y = -8 /:-7
y=8/7

x+ 2 * 8/7 = 7
y=8/7

x= 7 -16/7
y= 8/7

x=7 - 2 i 2/7 = 4 i 5/7
y = 8/7